Community perception towards dengue and dengue prevention program among residences of a rural settlement in Jempol, Negeri Sembilan - Abdul Rahman, Anita; Zainuddin, Huda; Minhat, Halimatus Sakdiah; Juni, Muhamad Hanafiah; Mazeli, Mohamad Iqbal (Community Health Society Malaysia, 2014)
Introduction: Dengue is a mosquito-borne infection which is a global health problem. The prevalence of dengue in Malaysia up to March 2014 showed an increasing trend in morbidity as well as mortality. Therefore this study was done to determine the perception on dengue and dengue prevention program among residents in a rural settlement. Methodology: A cross-sectional study design and based on cluster sampling, resident aged 18 years old and above was randomly chosen. Data was collected using assisted self- administered questionnaire that covered knowledge and the six subcomponents of the Health Belief Model (HBM) i.e. perceived susceptibility, perceived barrier, perceived benefits, perceived barriers, perceived self-efficacy and cues to act. Data was analyzed using SPSS version 21 of significant level α=.05. Results: A total of 306 residents’ participated the study giving a response rate of 96.8%. Approximately half of the respondents’ was female (57.6%), aged more than 50 years old (47.7%), had attained education up to secondary school (54.9%) and have lived in the settlement for 20 to 30 years (55.9%). Almost all the respondents were of Malay ethnicity and earn an income of less than RM2000 per month (92.2%). Majority of residents had correct knowledge on the cause of dengue (91.5%), symptoms of dengue (74-93.5%) and location of mosquitoes breeding (54.9- 98%). However, despite having good knowledge, one third of them perceived they have low susceptibility towards dengue, fogging activities is harmful and inconvenient as well as prevention of dengue fever should be handled totally by the government authorities. Conclusion: The study found that despite satisfactory knowledge on dengue and its preventive program, perception based on HBM that reflects the healthy behaviour among resident was still an issue that needs to be tackled to achieve successful prevention and control program.